2020
DOI: 10.1302/0301-620x.102b6.bjj-2019-1580.r1
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for manipulation under anaesthesia after total knee arthroplasty

Abstract: Aims Postoperative range of movement (ROM) is an important measure of successful and satisfying total knee arthroplasty (TKA). Reduced postoperative ROM may be evident in up to 20% of all TKAs and negatively affects satisfaction. To improve ROM, manipulation under anaesthesia (MUA) may be performed. Historically, a limited ROM preoperatively was used as the key harbinger of the postoperative ROM. However, comorbidities may also be useful in predicting postoperative stiffness. The goal was to assess preoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…Stiffness or arthrofibrosis after TKA ranges from 1.3% to 5.8% 19 , concurring with our results, but a previous paper suggested it might be more common for BCR TKA 20 . Stiffness was also more frequent in younger patients, which has been suggested in the literature before 21 . Our cohort had a higher rate of MUA than what is described, usually ranging from 1.5% to 4.8% of knees after TKA 19, [21][22][23] , which would be in line with that finding that stiffness might be a bigger issue in BCR TKA.…”
Section: Discussionsupporting
confidence: 61%
“…Stiffness or arthrofibrosis after TKA ranges from 1.3% to 5.8% 19 , concurring with our results, but a previous paper suggested it might be more common for BCR TKA 20 . Stiffness was also more frequent in younger patients, which has been suggested in the literature before 21 . Our cohort had a higher rate of MUA than what is described, usually ranging from 1.5% to 4.8% of knees after TKA 19, [21][22][23] , which would be in line with that finding that stiffness might be a bigger issue in BCR TKA.…”
Section: Discussionsupporting
confidence: 61%
“…The 2.3% (82 of 3558) of patients that underwent an MUA after unrestricted caliperverified KA TKA is comparable to or lower than the incidence of 6.5% (182 of 2783), 4.6% (164 of 3556), 3.6% (62 of 1729) reported after MA TKA performed in a single institution [4,6,9]. Because 2 to 6 out of a 100 TKAs undergo an MUA, the long-term risk of further surgery is of interest to the patient and surgeon [1,2] A registry study of 664,604 primary MA TKAs in which 3918 (0.6%) underwent MUA after a median of 2.0 +/− 1.0 months reported that revision surgery occurred in 131 (3.4%) MUA patients after a median of 9.0 months [1].…”
Section: Discussionmentioning
confidence: 79%
“…The reported incidence of MUA for stiffness after mechanically aligned (MA) TKA ranges from 1 to 12% [2][3][4]. Factors contributing to the risk of stiffness include component malposition, patients being younger, smoking, prior knee surgery, diabetes, use of anticoagulation drugs (i.e., warfarin), limited preoperative ROM, and a long tourniquet time [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we deemed it necessary to evaluate the factors affecting ROM after two-stage revision arthroplasty as a treatment for PJI. Previous studies reported that patient factors, such as causative diseases, degree of deformity, age, BMI, and pre-operative ROM, surgery-related factors, such as surgical approach and technique and component position and alignment, and other various factors, such as rehabilitation, may affect ROM after primary or revision TKA [ 19 , 20 , 31 33 ]. However, factors affecting ROM in two-stage revision arthroplasty for PJI may differ from those affecting ROM in conventional primary TKA.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, post-operative ROM is considered to be an important factor that can affect the satisfaction rate after TKA [ 14 18 ]. It has been reported that various factors, such as age, pre-operative ROM, and body mass index (BMI), are factors that can affect ROM after primary TKA [ 19 ], and Ritter et al [ 20 ] reported that these factors can also affect the postoperative ROM after revision TKA. However, Ritter et al [ 20 ] did not mention the exact reason why the revision TKA was done and just how many surgeries was performed, which is a weakness of their study.…”
Section: Introductionmentioning
confidence: 99%